A CaCDPK29–CaWRKY27b module promotes CaWRKY40‐mediated thermotolerance and immunity to Ralstonia solanacearum in pepper. Issue 4 (22nd December 2021) - Yang, Sheng; Cai, Weiwei; Shen, Lei; Cao, Jianshen; Liu, Cailing; Hu, Jiong; Guan, Deyi; He, Shuilin
Summary: CaWRKY40 in pepper ( Capsicum annuum ) promotes immune responses to Ralstonia solanacearum infection (RSI) and to high‐temperature, high‐humidity (HTHH) stress, but how it interacts with upstream signalling components remains poorly understood. Here, using approaches of reverse genetics, biochemical and molecular biology we functionally characterised the relationships among the WRKYGMK‐containing WRKY protein CaWRKY27b, the calcium‐dependent protein kinase CaCDPK29, and CaWRKY40 during pepper response to RSI or HTHH. Our data indicate that CaWRKY27b is upregulated and translocated from the cytoplasm to the nucleus upon phosphorylation of Ser137 in the nuclear localisation signal by CaCDPK29. Using electrophoretic mobility shift assays and microscale thermophoresis, we observed that, due to the replacement of Q by M in the conserved WRKYGQK, CaWRKY27b in the nucleus failed to bind to W‐boxes in the promoters of immunity‐ and thermotolerance‐related marker genes. Instead, CaWRKY27b interacted with CaWRKY40 and promoted its binding and positive regulation of the tested marker genes including CaNPR1, CaDEF1 and CaHSP24 . Notably, mutation of the WRKYGMK motif in CaWRKY27b to WRKYGQK restored the W‐box binding ability. Our data therefore suggest that CaWRKY27b is phosphorylated by CaCDPK29 and acts as a transcriptional activator of CaWRKY40 during the pepper response to RSI and HTHH.